Addressing the accountability challenges of international policing in peace support operations - Kearney, Jonathan A. (Crime, law and social change, 2011)
There is increasing concern over the behaviour and accountability of international personnel, including CIVPOL contingents, deployed in peace-keeping and peace-building missions throughout the world. From the point of view of local populations the ‘internationals’ are typically perceived to be ‘above the law’. This is directly related to the fact that under status of forces or mission agreements (SOFAs or SOMAs) they are exempt from local host state jurisdiction. There are also significant practical problems in gathering and presenting evidence for disciplinary or criminal proceedings in their home states. This paper will analyse these problems in detail, based on a study of some recent European Union and international missions and suggest how a more co-operative home and host state approach to monitoring, investigation and adjudication of alleged misconduct might achieve more effective accountability and thus contribute to the overall success of CIVPOL missions.